Characterisation of thermal runaway behaviour of cylindrical lithium-ion battery using Accelerating Rate Calorimeter and oven heating - Md Said, Mohamad Syazarudin; Mohd Tohir, Mohd Zahirasri (Elsevier, 2021)
In this work, thermal runaway of lithium-ion battery was characterised under adiabatic and non-adiabatic conditions using Accelerating Rate Calorimeter (ARC) and oven respectively. Battery with higher electrical capacity demonstrated a higher tendency to experience thermal runaway with shorter induction time and resulted with a more energetic response, as indicated by higher maximum temperature rise. Oven tests at 190 °C were able to capture thermal runaway characteristics in batteries with 100% state-of-charge (SOC) only and resulted in a maximum temperature of 738–783 °C. Two batteries were more inclined to suffer thermal runaway as the induction time was reduced by 8.6% to 115.98 min, compared to 126.92 min for single cell. A further inclined by 15% to 107.72 min was recorded for two batteries with parallel electrical connection. Meanwhile, ARC was able to induce thermal runaway in 50% SOC battery and instigated exothermic thermal decomposition in 0% SOC battery due to the longer heating process. The maximum temperatures recorded from ARC tests were between 404 and 522 °C, lower than oven tests since some of the battery energy content was released slowly during the long self-heating period, leaving the battery with less energy for rapid release during thermal runaway.